Intracellular monitoring by dendritic cells – a new way to stay informed – from a simple scavenger to an active gatherer - Christopher Herbst; Larry A. Harshyne; Botond Z. Igyártó (Frontiers in Immunology, 2022)
Dendritic cells (DCs) are required for the initiation of the adaptive immune response. Their ability to acquire antigens in the periphery is a critical step in this process. DCs express a wide variety of adhesion molecules and possess an extremely fluid plasma membrane that facilitates scavenging the extracellular environment and capturing material like exosomes, apoptotic bodies, and pathogens. Besides these standard routes, the acquisition of antigens by DCs can be further facilitated by tunneling nanotubes, trogocytosis, and gap junctions. However, in this article, we will argue that this is an incomplete picture, as certain observations in the literature cannot be explained if we assume DCs acquire antigens only through these means. Instead, it is more likely that DCs preferentially use adhesion molecules to form long-lasting cell-cell interactions to actively siphon material from cells they are in direct contact with. It is highly likely that DCs use this mechanism to continually capture membrane and cytosolic material directly from surrounding cells, which they scan to assess the health of the donor cell. Doing so would provide an array of advantages for the host immune system, as it would not be reliant on compromised cells to release antigens into the extracellular milieu. Therefore, we propose updating our view of DC antigen acquisition to include a process of active, contact-dependent capture of material directly from neighboring cell cytosol (cytocytosis), which we would term intracellular monitoring.